Effect of Elaeagnus Angustifolia Lozenge on Gag Reflex in Dental Patients - Ehsan Hekmatian; Elham Shadmehr; Gholamreza Asghari (Islamic Dental Association of Iran, 2012)
Background and Aim : Gag reflex is one of the most common problems in dental treatment. All researches performed to reduce or eliminate this reflex were not effective or were time-consuming. The aim of this study was to evaluate the use of Elaeagnus Angustifolia lozenge in controlling gag reflex during dental treatment .  Materials and Methods : This study was a randomized double blind controlled trial with convenient sampling on 84 patients that were candidates for radiographic procedures in the School of Dentistry, Isfahan University of Medical Sciences. The cases were randomly divided into two groups of case and control. The case group used Elaeagnus Angustifolia L extracts and the control group used placebo. Fruit extract was formed into lozenge. Before and after intervention, the gag reflex was evaluated by stimulation of the soft palate and pharyngeal tonsils. Data analysis and comparison was performed with SPSS 11 software and Chi-square , McNamara and t tests .  Results : The gag reflex significantly decreased in the soft palate region (p<0.001) and pharyngeal tonsils (p<0.001) in the intervention group. In the placebo group, decrease of gag reflex was not significant in any of these locations (p=0.9). The decrease in gag reflex in the soft palate and the pharyngeal tonsils in the case and control groups before and after the intervention showed statistically significant differences (P<0.01).  Conclusion : Elaeagnus Angustifolia L. extracts seem to be an effective method to control gag reflex during dental treatment. It may be a confident method to use on dental procedures, especially radiographic procedures.